Use of fast‐acting insulin aspart in insulin pump therapy in clinical practice. Issue 9 (19th June 2019) - Evans, Mark; Ceriello, Antonio; Danne, Thomas; De Block, Christophe; DeVries, J. Hans; Lind, Marcus; Mathieu, Chantal; Nørgaard, Kirsten; Renard, Eric; Wilmot, Emma G.
Abstract: Fast‐acting insulin aspart (faster aspart) is a novel formulation of insulin aspart (IAsp) containing the additional excipients niacinamide and L‐arginine. The improved pharmacological profile and greater early glucose‐lowering action of faster aspart compared with IAsp suggests that faster aspart may be advantageous for people with diabetes using continuous subcutaneous insulin infusion (CSII). The recent onset 5 trial was the first to evaluate the efficacy and safety of an ultra‐fast‐acting insulin in CSII therapy in a large number of participants with type 1 diabetes (T1D). Non‐inferiority of faster aspart to IAsp in terms of change from baseline in HbA1c was confirmed, with an estimated treatment difference (ETD) of 0.09% (95% CI, 0.01; 0.17; P < 0.001 for non‐inferiority [0.4% margin]). Faster aspart was superior to IAsp in terms of change from baseline in 1‐hour post‐prandial glucose (PPG) increment after a meal test (ETD [95% CI], −0.91 mmol/L [−1.43; −0.39]; P = 0.001), with statistically significant improvements also at 30 minutes and 2 hours. The overall rate of severe or blood glucose‐confirmed hypoglycaemia was not statistically significantly different between treatments, with an estimated rate ratio of 1.00 (95% CI, 0.85; 1.16). A numerical imbalance in severe hypoglycaemic episodes between faster aspart and IAsp was seen in the treatment (21 vs 7) and the 4‐week run‐in periods (4 vs 0). Experience from clinical practice indicates that all pump settings should be reviewed when initiating faster aspart with CSII, and that the use of continuous glucose monitoring or flash glucose monitoring, along with a good understanding of meal content and bolus type, may also facilitate optimal use. This review summarizes the available clinical evidence for faster aspart administered via CSII and highlights practical considerations based on clinical experience that may help healthcare providers and individuals with T1D successfully initiate and adjust faster aspart with CSII.